Systematic Literature Review:Research on Basketball Sports Biomechanics Using VOSviewer in the Scopus Database from 2015 to 2025 - Desto, Mochamad Krisna; Hakim, Abdul Aziz; Widodo, Achmad (UNIVERSITAS NEGERI MAKASSAR, 2025)
The era of modern sports science, biomechanics plays a crucial role in enhancing athletic performance, particularly in basketball. Biomechanics examines human body movements based on mechanical principles, which are applicable to fundamental techniques such as passing, shooting, dribbling, and jump shots to improve efficiency and prevent injuries. This study conducts a bibliometric review of basketball biomechanics literature indexed in the Scopus database from 2015 to 2025 using the VOSviewer software. The analysis includes publication trends, citation counts, author collaboration, and keyword and abstract term mapping. The results show fluctuating trends in both publications and citations, with a peak in publications in 2020 followed by a decline since 2022. Author collaboration is identified in two main clusters, indicating a well-organized research structure. Dominant keywords relate to injury, motion biomechanics, and applications in basketball and rehabilitation. Abstract terms are grouped into several thematic clusters, reflecting the diversity of research focuses. This study provides a comprehensive and systematic overview of the research landscape in basketball biomechanics, serving as a foundation for further evidence-based research and training development.